Acceleration and deceleration profiles: comparison between the 5-0-5 test and seasonal peak player performance - Pimenta, R.; Antunes, H.; Nakamura, F. Y. (Sports, 2026)
Change-of-direction (COD) capacity is a key performance metric in football due to the high volume of COD actions occurring during match play. This study aimed to (i) evaluate the repeatability of the 5-0-5 test and (ii) examine the relationship between acceleration and deceleration profiles of the 5-0-5 test and in-season peak performance. Nineteen national-level Portuguese football players competing in the under-23 Portuguese National Championship were analysed. Repeatability analysis was conducted using intraclass correlation coefficients (ICC). Paired-samples t-tests and Pearson correlations (r) were employed to assess within-subject differences and associations between 5-0-5 measures (highest accelerations from a standing start [ACC_S], deceleration prior to the change in direction (DEC_COD), acceleration after decelerating and changing direction [ACC_COD]) and seasonal peak performances (ACCmax). The in-season peak values were determined from the average of the three maximal values that occurred either in training sessions or in matches. Normalized (relative to seasonal performance) parameters showed good repeatability (ICC = 0.76-0.85). The best ACC_COD and DEC_COD were not significantly different from ACCmax [ACC_COD] vs. ACCmax: (5.04 ± 0.39 m/s2 vs. 5.36 ± 0.54 m/s2; p > 0.05) and DECmax [DEC_COD] vs. DECmax: (-6.47 ± 0.26 m/s2 vs. -6.35 ± 0.61 m/s2; p > 0.05), respectively. The average and best 5-0-5 ACC_S performances showed significant, moderate correlations (r = 0.48; p = 0.040 and r = 0.50; p = 0.028, respectively) with the players` peak in-season acceleration performance. Therefore, the best ACC_S and ACC_COD attempts can reflect values above 90% of ACCmax, while DEC_COD reflects values above 100% of DECmax and may assist in monitoring and tailoring training for this capacity on an individual basis.